The Effect Of Zakat On Indonesia's Social Capital - Irhamsyah Putra; Deni Nugraha; Muhammad Abdul Ghani Fakih (Institute of Computer Science (IOCS), 2022)
The purpose of this paper is to empirically analyze the effect of national zakat collection on the strength of the social capital of Indonesia. This research uses simple linear regression with time series data in annual form. The sample in this study is a saturated sample, which means that the entire population is the sample of this study. The data taken is secondary data taken from the National Zakat Statistics issued by BAZNAS and the Global Sustainable Competitiveness Index (GSCI) report issued by SolAbility. The results of the study show that there is a significant influence between the collection of national zakat on the social capital of Indonesia.